Composite Materials Engineering, Volume 2 Different Types of Composite Materials - Yi, Xiao-Su; Du, Shanyi; Zhang, Litong (Springer Nature Singapore : Imprint: Springer, 2018)
In two volumes, this book provides comprehensive coverage of the fundamental knowledge and technology of composite materials. This second volume reviews the research developments of a number of widely studied composite materials with different matrices. It also describes the related process technology that is necessary for a successful production. This work is ideal for graduate students, researchers, and professionals in the fields of materials science and engineering, as well as mechanical engineering.